Peristomal skin complications: causes, effects, and treatments - Doctor K; Colibaseanu DT (Chronic Wound Care Management and Research, 2016)
Kimberly Doctor, Dorin T Colibaseanu Section of Colon and Rectal Surgery, Mayo Clinic, Jacksonville, FL, USA Abstract: Enterostomal formation remains a necessary part of multiple types of surgeries. Stomal difficulties can be a source of frustration for patients; however, a properly functioning stoma in a patient educated in its care can result in a highly functional individual, with a high quality of life, comparable to a person without a stoma. Correct surgical technique is vital to creating a stoma that is sufficiently everted, and in a good anatomical location. Loop ileostomies have a higher chance of complications, thus care in their formation is especially important. Systemic disease (inflammatory conditions, and autoimmune diseases especially) as well as local conditions (pyoderma gangrenosum, infections, and fistulas, among others) can be the causes for difficult-to-treat peristomal complications. Accurate diagnosis is essential in order to be able to address the underlying disease. Choosing the appropriate products to care for the stoma is often a process of trial and error, and is best done under the guidance of an enterostomal therapist. This is especially true for stomas in overweight individuals or stomas that have become flush with the skin with time and changing body habitus. Inattention to care can result in problems that range from simple mucocutaneous separations (separation of the bowel edge from the surrounding skin) to large and difficult-to-heal ulcers. This article provides a systematic review of the most common challenges that patients with stoma are faced with, and offers solutions based on up-to-date review of the literature. Keywords: stoma care, stoma complications, stoma wound